Understanding the drivers of interprofessional collaborative practice among HIV primary care providers and case managers in HIV care programmes. Issue 3 (4th May 2017) - Mavronicolas, Heather A.; Laraque, Fabienne; Shankar, Arti; Campbell, Claudia
ABSTRACT: Care coordination programmes are an important aspect of HIV management whose success depends largely on HIV primary care provider (PCP) and case manager collaboration. Factors influencing collaboration among HIV PCPs and case managers remain to be studied. The study objective was to test an existing theoretical model of interprofessional collaborative practice and determine which factors play the most important role in facilitating collaboration. A self-administered, anonymous mail survey was sent to HIV PCPs and case managers in New York City. An adapted survey instrument elicited information on demographic, contextual, and perceived social exchange (trustworthiness, role specification, and relationship initiation) characteristics. The dependent variable, perceived interprofessional practice, was constructed from a validated scale. A sequential block wise regression model specifying variable entry order examined the relative importance of each group of factors and of individual variables. The analysis showed that social exchange factors were the dominant drivers of collaboration. Relationship initiation was the most important predictor of interprofessional collaboration. Additional influential factors included organisational leadership support of collaboration, practice settings, and frequency of interprofessional meetings. Addressing factors influencing collaboration among providers will help public health programmes optimally design their structural, hiring, and training strategies to foster effective social exchanges and promote collaborative working relationships.